Axillary lymph node dissection combined with radiotherapy for trichilemmal carcinoma with giant lymph node metastasis: A case report - Lv, Wenjie; Zheng, Dawen; Guan, Wenbin; Wu, Ping (Frontiers in Oncology, 2022)
Background Trichilemmal carcinoma (TC) is a rare malignancy with a poor outcome if local recurrence and distant metastasis occur. There is no treatment strategy for such a disease. Case presentation We reported a complicated case of TC in the right lower abdomen with ipsilateral axillary and inguinal lymph node metastases. After surgery and radiotherapy, there has been no recurrence or metastasis in the follow-up to date. Conclusion We believe that even though considered a tumor of low malignant potential, TC still has the risk of recurrence and metastasis, and the lymph node status should be identified if a high suspicion or diagnosis is made. Regional lymph node dissection followed by local radiotherapy is recommended as the optimal treatment strategy for patients with lymph node metastases of TC. Screening for metastasis and close follow-up are indispensable for improving prognosis.